2013
DOI: 10.1590/s0104-66322013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Erwinia carotovora l-asparaginase II production in Escherichia coli fed-batch cultures

Abstract: -Asparaginases are the cornerstone therapy of many successful combination regimens for the treatment of acute lymphoblastic leukemia (ALL), the most common malignancy in children and adolescents. The aim of this work was to produce recombinant Erwinia carotovora L-asparaginase II in Escherichia coli fed-batch cultures. Using a robust fed-batch technique with pre-determined exponential feeding rates, our bioreactor culture system yielded 30.7 grams of dry cell weight and 0.9 grams of soluble rErAII protein per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
19
0
3
Order By: Relevance
“…The present source of L-asparaginase was pharmaceutically may be a relevant alternative because L-asparaginase with low Km values was preferable for anti-cancer therapy [27] .…”
Section: Resultsmentioning
confidence: 99%
“…The present source of L-asparaginase was pharmaceutically may be a relevant alternative because L-asparaginase with low Km values was preferable for anti-cancer therapy [27] .…”
Section: Resultsmentioning
confidence: 99%
“…The combination of recombinant DNA technology and HDC in the fed-batch process, allows enzyme production in much larger quantities than those obtained in traditional processes (Nakagawa et al, 1995; Roth et al, 2013) and enabled the reduction of the culture volume from 20,000 to 300 L in the Medac's Spectrila® production process (European Medicines Agency, 2015; Wacker Biotech, 2016). The application of this technology to the production of ASNase with the optimization of the cultivation process and an effective purification strategy increased the productivity, the yield and the quality of the ASNase produced, reducing the overall production costs while contributing to the technical-economic feasibility of the process.…”
Section: L-asparaginase Manufacturing: Production Process and Purificmentioning
confidence: 99%
“…The K m value of rBliAIII is 0.67×10 −3 M which showed that it has a good substrate affinity toward Lasparagine. rBliAIII has a good affinity toward the substrate when compared to various [42] Kinetic parameters like K m , k cat , and k cat /K m of E. coli, Erwinia spp., and B. licheniformis (present study) Lasparaginase have been compared microbial asparaginases. rBliAIII can serve as a potential substitute for the commercially available asparaginase sources.…”
Section: Resultsmentioning
confidence: 99%